Heat and momentum diffusion of ternary hybrid nanoparticles in a channel with dissimilar permeability's and moving porous walls: A Multi-linear regression - Se-Jin Yook; C.S.K. Raju; Bander Almutairi; S.U. Mamatha; Nehad Ali Shah; Sayed M. Eldin (Case Studies in Thermal Engineering, 2023)
In recent times, the term Hybrid nanofluid is frequently used owing to its extraordinary influence on different science and engineering processes like therapeutic process, motorized investigational and electrical circuits where energy transference is significant and marine engineering etc. The objective of the present investigation is to supervise the heat and momentum diffusion of ternary hybrid nanoparticles in a channel with dissimilar permeability's and moving porous walls which enables the nanofluid to enter or exist during successive expansion or contractions. In this model, newly proposed Wu's slip circumstance is enforced on the down permeable wall of the channel and analyzed along with thermal radiation and convective heating. The flow and heat diffusion of ternary hybrid flow-1 (Carbon Nanotubes(CNT), Graphene, Aluminum oxide), ternary hybrid flow-2 (Copper oxide, Copper, magnetite), ternary hybrid nanofluid 3 (Paraffin wax, Sand, AA7072 aluminum alloy) water as base fluid is compared and analyzed. The unsteady Navier Stokes equations is converted to partial differential equation by via stream function and the vorticity equation further similarity conversions are used to convert the prevailing flow quantities into non-linear differential equations and then elucidated numerically by shooting procedure with Runge-Kutta (R-K 4th order). Linear Regression method (LRM) is used to model the solution for the flow variables. Outcomes obtained for axial velocity f′(χ) and temperature circulation θ(χ) are interpreted by the graph. Achieved outcomes are compared with existing studies. The topmost result of this investigation is found to be -The higher distribution of heat transmission rate is observed in Case-3 (Paraffin wax + Sand + AA7072) with rise in Bi, Since the particles interaction is higher. The second order slip is shown lesser friction in the Copper oxide + copper + magnetite compared to rest of the situations